The Effectness Of Syntax Learning Media On Achieving Indonesian Language Curriculum Competance - Eva Juliana (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The purpose of this study is to examine the effectiveness of syntax learning media in improving the achievement of Indonesian language curriculum competencies. The methodology used is a literature study that reviews various articles and journals related to the influence of learning media on students' understanding of syntax and competencies. The results of the analysis indicate that the use of syntax learning media significantly improves students' conceptual understanding and linguistic skills, and supports optimal achievement of curriculum competencies. These findings reinforce the importance of utilizing innovative media in the Indonesian language learning process, especially syntax. Thus, syntax learning media is effective in improving student learning outcomes and supporting the achievement of curriculum competencies as a whole.